Peran Bank Syariah Pada Masa Pandemi Covid-19 - Cahyono, Andi; Siregar, Erwin; Wati, Asiah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to determine the effectiveness of social funds in Islamic banks against MSMEs due to the Covid-19 pandemic. The approach used in this research is descriptive qualitative. The techniques used are content analysis and library research. The results of this study indicate that Micro, Small, and Medium Enterprises (MSMEs) receive assistance from zakat, infaq, and sadaqah. Apart from leading business capital assistance for the business sector or Micro, Small and Medium Enterprises (MSMEs) from the government for Micro, Small and Medium Enterprises (MSMEs) that already have a business permit from the village, as well as through the qardhul hasan scheme and loans for businesses that exist in Islamic banks. . So far, the social funds in Islamic banks for Micro, Small and Medium Enterprises (MSMEs) have not been effective because people use more funds to fulfill basic needs.